2010
DOI: 10.1021/jf104012z
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity and Inhibition of Lipid Peroxidation in Germinating Seeds of Transgenic Soybean Expressing OsHGGT

Abstract: Tocochromanols are potent lipid-soluble antioxidants and essential nutrients for human health. Genetic engineering techniques were used to develop soybeans with enhanced vitamin E levels, including tocotrienols, which are not found in soybean. The gene encoding rice homogentisate geranylgeranyl transferase (HGGT) was overexpressed in soybeans using seed-specific and constitutive promoters. The association between abundance of vitamin E isomers and antioxidant activity was investigated during seed germination. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 35 publications
(42 reference statements)
2
19
0
1
Order By: Relevance
“…Gamma- and delta-tocotrienols, which were not detected in wild-type soybean seeds, were present in transgenic soybean seed cultivars. The same study also showed that alpha-tocotrienol, which was not present in non-germinated transgenic soybean seeds, was detected in some transgenic lines after three days of germination [58]. It is clear that most studies have used HPLC itself to investigate the presence of tocopherols and tocotrienols; however, in the last few years, some research teams [39,59] have used HPLC-MS for identification and quantification purposes, which is useful in providing a complete picture for the presence of these high-valued molecules.…”
Section: Impact Of New Cultivars On the Content Of Tocopherols Andmentioning
confidence: 98%
“…Gamma- and delta-tocotrienols, which were not detected in wild-type soybean seeds, were present in transgenic soybean seed cultivars. The same study also showed that alpha-tocotrienol, which was not present in non-germinated transgenic soybean seeds, was detected in some transgenic lines after three days of germination [58]. It is clear that most studies have used HPLC itself to investigate the presence of tocopherols and tocotrienols; however, in the last few years, some research teams [39,59] have used HPLC-MS for identification and quantification purposes, which is useful in providing a complete picture for the presence of these high-valued molecules.…”
Section: Impact Of New Cultivars On the Content Of Tocopherols Andmentioning
confidence: 98%
“…Gene abbreviations: 1-deoxy-D-xylulose-5-phosphate synthase (dxs2 and 3); arogenate/prephenate dehydrogenase family protein (arodeH2); solanesyl diphosphate synthase (sds); phytol kinase (vte5); phytol phosphate kinase (vte6); p-hydroxyphenylpyruvate dioxygenase (hppd1); homogentisate geranylgeranyltransferase (hggt1); MPBQ/MSBQ/MGGBQ methyltransferase (vte3); and g-tocopherol methyltransferase (vte4). that of tocopherols (Cahoon et al, 2003;Kim et al, 2011;Yang et al, 2011;Zhang et al, 2013;Tanaka et al, 2015). In contrast, engineering total tocopherol content is more difficult, and even with coordinate overexpression of multiple pathway steps, the increases achieved were modest (Savidge et al, 2002;Collakova and DellaPenna, 2003;Karunanandaa et al, 2005;Raclaru et al, 2006;Lu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Finely ground soybeans (2 g) were placed in a Soxtherm automatic extraction unit (Gerhardt, Germany) and extracted with 140 mL n ‐hexane:EtOAc (85:15, v/v, containing 0.1 g L −1 BHT) at 180 °C for 110 min under dim light conditions. Crude lipid extracts were diluted to 50 mL and passed through a 0.2 µm filter unit (Millipore, Billerica, MA, USA) prior to HPLC analysis . For seed germination, the direct extraction method was modified .…”
Section: Methodsmentioning
confidence: 99%